The Researcher–Practitioner Partnership Study (RPPS): Experiences From Criminal Justice System Collaborations Studying Violence Against Women. (June 2017) - Sullivan, Tami P.; Price, Carolina; McPartland, Tara; Hunter, Bronwyn A.; Fisher, Bonnie S.
The benefits of researcher–practitioner (R-P) collaborations focused on violence against women (VAW) are many. Such projects support researchers and practitioners working together to create uniquely comprehensive projects that have the potential to change practices, policies, and services. Extant literature is limited in that it has (a) focused on the experiences of a very limited number of collaborations, (b) ignored collaborations conducted in the context of the criminal justice system, and (c) excluded as a focus the products that result from the collaborations and their dissemination. Therefore, the goal of this qualitative study is to identify the essential elements to consider for successful R-P collaborations on VAW research in the criminal justice system.